PENERAPAN METODE DISKUSI UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS DAN PEMECAHAN MASALAH - W Widiastuti; W Kania (Jurnal Pendidikan Ekonomi Indonesia, 2021)
This research is motivated by the low ability to think critically and solve students' problems in economics subjects, so this aims to find out how much improvement in students' critical thinking skills and problem-solving using the discussion method. This research is a type of qualitative research. The sample in this study consisted of 35 students in class X-12 in the odd semester for the 2021-2022 academic year. Data obtained from observations during the learning process and the results of critical evaluation and problem-solving. The results showed that: (1) there was an increase in the criticality of students from cycle 1 to cycle 2 (2) there was an increase in the problem-solving ability of students from cycle 1 to cycle 2. The results of this study recommend the use of the discussion method in improving critical thinking skills and solution to problem.